A High-Field Anodic NiO Nanosponge with Tunable Thickness for Application in p-Type Dye-Sensitized Solar Cells - Sultan, Umair; Ahmadloo, Farzaneh; Cha, Gi; Gökcan, Baris; Hejazi, Seyedsina; Yoo, Jeong Eun; Nguyen, Nhat Truong; Altomare, Marco; Schmuki, Patrik; Killian, Manuela (ACS Applied Energy Materials, 2020)
Dye-sensitized photocathodes have the potential to significantly contribute to the efficiency of the solar light-to-current conversion in tandem dye-sensitized solar cells (DSSCs). A novel, highly porous nanoarchitecture of NiO is developed in this project. The spongelike material is grown by anodization, shows a virtually crack-free morphology, strongly adheres to the substrate, and can be grown with a controllable thickness of at least up to 6.5 mu m. The oxide composition is NiO and the nanosponge exhibits p-type semiconductive behavior. A doubling of the maximum reported p-type DSSC efficiency compared to coumarin C343-sensitized NiO nanoparticle photocathodes can be achieved with the NiO nanosponge. The developed dye-sensitized p-type NiO-based cathodes are promising for application as photocathodes in tandem DSSC devices.
CRIS-Team WoS Importer:2020-09-18

A long-term stable aqueous aluminum battery electrode based on one-dimensional molybdenum-tantalum oxide nanotube arrays - Jin, Bowen; Hejazi, Seyedsina; Chu, Hongqi; Cha, Gi; Altomare, Marco; Yang, Min; Schmuki, Patrik (Nanoscale, 2021)
Aluminum ion aqueous batteries (AIBs) are among the most promising candidates for high energy density devices due to the multivalent redox processes associated with Al3+ ion intercalation. However, only a few stable AIB electrode materials have been reported so far. MoO3 is a very promising electrode material due to its octahedral layered crystal structure which can accommodate multivalent cation by intercalation. However, the poor electrochemical stability of MoO3 and the sluggish intercalation kinetics of Al3+ ion in Mo oxides electrodes limit its practical application. In this work, we propose a strategy to overcome such shortcomings of MoO3 by fabricating electrodes composed of self-ordered one-dimensional (1D) MoTaOx nanotubes synthesized via electrochemical anodization of Mo-Ta alloy substrates. We show that this approach allows for direct incorporation of Ta in the Mo oxide nanotubes. The resulting MoTaOx nanotubes, composed of octahedral MoO3 and rhombohedral Mo2Ta2O11 phases, exhibit remarkable electrochemical stability and Al-ion storage properties in aqueous electrolytes that are superior to that of pristine Mo oxide or other most efficient electrode materials reported to date. Such MoTaOx nanotube-based electrodes can achieve a specific capacity of 1180 mA h cm-3 (337 mA h g-1, 141 µA h cm-2) at 1.25 A cm-3 ( 0.35 A g-1, 0.15 mA cm-2). More importantly, the capacity retention of such nanotube array electrodes remains above 83% of the initial capacity after 3000 cycles.
CRIS-Team Scopus Importer:2021-04-16

Anodic nanoporous niobium oxide layers grown in pure molten ortho-phosphoric acid - Altomare, Marco; Cha, Gi; Schmuki, Patrik (Electrochimica Acta, 2020)
The anodic oxidation of niobium is investigated in pure molten ortho-phosphoric acid (o-H3PO4). At applied potentials in the 2.5–60 V range and for electrolyte temperatures in the 60–110 °C range, porous niobium oxide layers are formed. Pore ordering and morphology depend on the anodization voltage, time and temperature, i.e. the anodic oxide develops different morphologies depending on low- or high-field anodizing conditions. At 100 °C and low voltages, e.g. ≤ 5 V, vertically oriented, amorphous oxide nanopores with cylindrical shape (“nanochannels”) grow with an average diameter of 5–8 nm. Higher voltages (10–20 V) lead to a less ordered pore morphology, resembling a “fish bone” structure. At 40–60 V, and after a sufficiently long anodization time (≥30 min), an orthorhombic Nb2O5 hierarchical structure forms that shows a bimodal pore size distribution with some 100 nm wide main pores that branch out into ∼ 10 nm wide side nanochannels. A partial crystallization of the anodic oxide is observed at high voltages (≥40 V). We propose that this is due to a high field-induced crystallite nucleation in the barrier oxide at the oxide/metal interface. With time, the crystalline oxide is incorporated in the porous layer. The main pores, partially crystalline and hence more stable in the anodizing electrolyte, result from the gradual dissolution of the amorphous side nanochannels.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Anodization; High field induced crystallization; Ortho-phosphoric acid; Porous niobium oxide; Self-organizing electrochemistry

As a single atom Pd outperforms Pt as the most active co-catalyst for photocatalytic H2 evolution - Cha, Gi; Hwang, Imgon; Hejazi, Seyedsina; Dobrota, Ana S.; Pašti, Igor A.; Osuagwu, Benedict; Kim, Hyesung; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdeněk; Kment, Štěpán; Mohajernia, Shiva; et al. (iScience, 2021)
Here, we evaluate three different noble metal co-catalysts (Pd, Pt, and Au) that are present as single atoms (SAs) on the classic benchmark photocatalyst, TiO2. To trap the single atoms on the surface, we introduced controlled surface vacancies (Ti3+-Ov) on anatase TiO2 nanosheets by a thermal reduction treatment. After anchoring identical loadings of single atoms of Pd, Pt, and Au, we measure the photocatalytic H2 generation rate and compare it to the classic nanoparticle co-catalysts on the nanosheets. While nanoparticles yield the well-established the hydrogen evolution reaction activity sequence (Pt > Pd > Au), for the single atom form, Pd radically outperforms Pt and Au. Based on density functional theory (DFT), we ascribe this unusual photocatalytic co-catalyst sequence to the nature of the charge localization on the noble metal SAs embedded in the TiO2 surface.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Catalysis; Materials characterization; Nanomaterials

Comparison of Anodic TiO2-Nanotube Membranes used for Frontside-Illuminated Dye-Sensitized Solar Cells - Mohammadpour, Fatemeh; Moradi, Mahmood; Cha, Gi; So, Seulgi; Lee, Kiyoung; Altomare, Marco; Schmuki, Patrik (ChemElectroChem, 2015)
In the present work we compare TiO2-nanotube lift-off strategies for the construction of frontside-illuminated dye-sensitized solar cells (DSSCs). Anodic nanotube layers were detached from the metallic back contact by using different techniques and transferred onto a fluorine-doped tin oxide substrate. We show that if we use an optimized potential step treatment to fabricate membranes, DSSC efficiencies can be significantly increased ( extgreekh>8 %). The improved efficiency is ascribed to higher specific dye loading and enhanced electron-transport properties of optimally fabricated TiO2-nanotube membranes.
EAM Import::2019-03-13

Development of non-enzymatic cholesterol bio-sensor based on TiO2 nanotubes decorated with Cu2O nanoparticles - Khaliq, Nilem; Rasheed, Muhammad Asim; Cha, Gi; Khan, Maaz; Karim, Shafqat; Schmuki, Patrik; Ali, Ghafar (Sensors and Actuators B-Chemical, 2020)
A novel amperometric non-enzymatic cholesterol biosensor based on Cu2O-TiO2 hybrid nanostructure has been studied. TiO2 nanotubes (TNTs) were synthesized via anodization of titanium (Ti) foils and subsequently decorated with Cu2O nanoparticles (NPs) using chemical bath deposition (CBD) method. Incorporation of Cu2O NPs on TNTs have resulted in the high electroactive surface area which enhanced the electron transfer rate at the surface of the electrode. Cyclic voltammetry (CV) and amperometric response of the fabricated electrode exhibited high catalytic activity towards the cholesterol oxidation. The hybrid electrode demonstrated 5-fold increase in the sensitivity (∼6034.04 μAmM−1 cm−2) compared to pristine with low detection limit (∼0.05 μM) and fast response time (3 s). Moreover, the real time analysis of the cholesterol in human blood serum offered favorable accuracy with reference to the commercially available cholesterol biosensors. This study shows potential application of Cu2O NPs decorated TNTs for the development of highly stable, reproducible, and selective biosensor.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Amperometry; Biosensor; Cholesterol; Copper oxide; Titanium oxide nanotubes

Enhanced performance of dye-sensitized solar cells based on TiO2 nanotube membranes using an optimized annealing profile - Mohammadpour, F.; Moradi, M.; Lee, Kiyoung; Cha, Gi; So, Seulgi; Kahnt, Axel; Guldi, Dirk Michael; Altomare, Marco; Schmuki, Patrik (Chemical Communications, 2015)
We use free-standing TiO2 nanotube membranes that are transferred onto FTO slides in front-side illuminated dye-sensitized solar cells (DSSCs). We investigate the key parameters for solar cell arrangement of self-ordered anodic TiO2 nanotube layers on the FTO substrate, namely the influence of the annealing procedure on the DSSC light conversion efficiency. The results show that using an optimal temperature annealing profile can significantly enhance the DSSC efficiency (in our case extgreekh = 9.8%), as it leads to a markedly lower density of trapping states in the tube oxide, and thus to strongly improved electron transport properties.
EAM Import::2019-03-14

Establishing High Photocatalytic H-2 Evolution from Multiwalled Titanate Nanotubes - Yoo, Jeong Eun; Alshehri, Abdulmohsen Ali; Qin, Shanshan; Bawaked, Salem Mohamed; Mostafa, Mohamed Mokhtar M.; Katabathini, Narasimharao; Fehn, Dominik; Schmidt, Jochen; Mazare, Anca Valentina; Denisov, Nikita; Cha, Gi; Meyer, Karsten; et al. (ChemCatChem, 2020)
Black TiO2 in various forms has been investigated for numerous photochemical applications. In photocatalytic water splitting, "grey" titania forms have been reported to reach considerable H-2 generation rates without using a noble metal co-catalyst. Up to now, a variety of anatase powders or other morphologies has been investigated in grey and black forms. Here we describe that hydrothermal titanate/anatase nanotubes can show a strong noble metal free photocatalytic activity. For optimized "blackening" conditions, a drastically higher photocatalytic H-2 production can be obtained than for other nanoscale morphologies. This effect can further be improved with a very mild Pt doping that again shows a clearly stronger photocatalytic H-2 production than comparably loaded nanopowders.
CRIS-Team WoS Importer:2020-05-15

Free-Standing Membranes to Study the Optical Properties of Anodic TiO2 Nanotube Layers - Cha, Gi; Schmuki, Patrik; Altomare, Marco (Chemistry - An Asian Journal, 2016)
In the present work we investigate various optical properties (such as light absorption and reflectance) of anodic TiO2 nanotube layers directly transferred as self-standing membranes onto quartz substrates. This allows investigation in a transmission geometry which provides significantly more reliable data than measurements on the metallic Ti substrate. Light transmission and reflectance measurements were carried out for layers of thickness varying from 1.8 to 50 extgreekmm, and the layers were investigated in their amorphous and crystalline forms. A series of wavelength-dependent light attenuation coefficients are extrapolated and found to match the photocurrent versus irradiation wavelength behavior. A feature specific to anodic nanotubes is that their intrinsic carbon contamination content causes a proportional sub-bandgap response. Overall, the extracted data provide a valuable basis and understanding for the design of photo-electrochemical devices based on TiO2 nanotubes. In the present work we investigate various optical properties (such as light absorption and reflectance) of anodic TiO2 nanotube layers directly transferred as self-standing membranes onto quartz substrates. This allows investigation in a transmission geometry which provides significantly more reliable data than measurements on the metallic Ti substrate. Light transmission and reflectance measurements were carried out for layers of thickness varying from 1.8 to 50 extgreekmm, and the layers were investigated in their amorphous and crystalline forms. A series of wavelength-dependent light attenuation coefficients are extrapolated and found to match the photocurrent versus irradiation wavelength behavior. A feature specific to anodic nanotubes is that their intrinsic carbon contamination content causes a proportional sub-bandgap response. Overall, the extracted data provide a valuable basis and understanding for the design of photo-electrochemical devices based on TiO2 nanotubes.
EAM Import::2019-03-14

Inducing a Nanotwinned Grain Structure within the TiO2 Nanotubes Provides Enhanced Electron Transport and DSSC Efficiencies >10% - So, Seulgi; Hwang, Imgon; Yoo, Jeong Eun; Mohajernia, Shiva; Mackovic, Mirza; Spiecker, Erdmann; Cha, Gi; Mazare, Anca Valentina; Schmuki, Patrik (Advanced Energy Materials, 2018)
Titania is one of the key materials used in 1D, 2D, and 3D nanostructures as electron transport media in energy conversion devices. In the present study, it is shown that the electronic properties of TiO2 nanotubes can be drastically improved by inducing a nanotwinned grain structure in the nanotube wall. This structure can be exclusively induced for “single-walled” nanotubes with a high-temperature treatment in pure oxygen atmospheres. Nanotubes with a twinned grain structure within the tube wall show a strongly enhanced conductivity and photogenerated charge transport compared to classic nano-tubes. This remarkable improvement is exempliﬁed in the electronic properties by using nanotwinned TiO2 nanotubes in dye-sensitized solar cells where a signiﬁcant increase in efﬁciency of up to 10.2% is achieved. <p
Keywords: nanotwinned; TiO2 nanotubes; conductivity; DSSCs

Li+ doped anodic TiO2 nanotubes for enhanced efficiency of Dye-sensitized solar cells - Cha, Gi; Özkan, Selda; Hwang, Imgon; Mazare, Anca Valentina; Schmuki, Patrik (Surface Science, 2022)
The insertion of cations such as H+ and Li+ to TiO2 photoelectrodes is a universally recognized method to enhance the electric conductivity of TiO2 electrodes. In the present work we report on the fabrication and use of Li+ inserted TiO2 nanotubes (NTs) as a photoanode scaffold in dye-sensitized solar cells (DSSCs). Li+ was successfully inserted into the TiO2 NTs by a cathodic treatment in 1 M LiClO4/ethylene carbonate (EC) electrolyte. We observe for DSSCs fabricated from such nanotubes an overall solar cell efficiency of ∼7.1% compared to an efficiency of ∼5.7% for the non Li-intercalated electrode. We ascribe this enhancement to a faster electron transport and an increased conductivity in the lithiated TiO2 NTs.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Anodization; Dye-sensitized solar cell (DSSC); Li ion intercalation; TiO

Li+ Pre-Insertion Leads to Formation of Solid Electrolyte Interface on TiO2 Nanotubes That Enables High-Performance Anodes for Sodium Ion Batteries - Cha, Gi; Mohajernia, Shiva; Nguyen, Nhat Truong; Mazare, Anca Valentina; Denisov, Nikita; Hwang, Imgon; Schmuki, Patrik (Advanced Energy Materials, 2019)
Recently, sodium ion batteries (SIBs) have been widely investigated as one of the most promising candidates for replacing lithium ion batteries (LIBs). For SIBs or LIBs, designing a stable and uniform solid electrolyte interphase (SEI) at the electrode–electrolyte interface is the key factor to provide high capacity, long-term cycling, and high-rate performance. In this paper, it is described how a remarkably enhanced SEI layer can be obtained on TiO2 nanotube (TiO2 NTs) arrays that allows for a strongly improved performance of sodium battery systems. Key is that a Li+ pre-insertion in TiO2 NTs can condition the SEI for Na+ replacement. SIBs constructed with Li-pre-inserted NTs deliver an exceptional Na+ cycling stability (e.g., 99.9 ± 0.1% capacity retention during 250 cycles at a current rate of 50 mA g−1) and an excellent rate capability (e.g., 132 mA h g−1 at a current rate of 1 A g−1). The key factor in this outstanding performance is that Li-pre-insertion into TiO2 NTs leads not only to an enhanced electronic conductivity in the tubes, but also expands the anatase lattice for facilitated subsequent Na+ cycling.
CRIS-Team Scopus Importer:2019-12-31
Keywords: anodization; pre-lithiation; sodium ion batteries; solid electrolyte interphases; TiO

Optimized Pt Single Atom Harvesting on TiO2 Nanotubes—Towards a Most Efficient Photocatalyst - Wu, Zhenni; Hwang, Imgon; Cha, Gi; Qin, Shanshan; Tomanec, Ondřej; Badura, Zdenek; Kment, Stepan; Zboril, Radek; Schmuki, Patrik (Small, 2021)
In the present work the authors show that anodic TiO2 nanotubes (NT) show excellent harvesting properties for Pt single atoms (Pt SAs) from highly dilute Pt solutions. The tube walls of anodic nanotubes, after adequate annealing to anatase, provide ample of suitable trapping sites—that is, surface Ti3+-Ov (Ov: oxygen vacancy) defects that are highly effective to extract and accumulate Pt in the form of SAs. A saturated (maximized) SA density can be achieved by an overnight immersion of a TiO2 NT layer to a H2PtCl6 solution with a concentration that is as low as 0.01 mm Pt. Such TiO2 NTs with surface trapped Pt SAs provide a maximized high activity for photocatalytic H2 generation (reaching a turnover frequency (TOF) of 1.24 × 106 h−1 at a density of 1.4 × 105 Pt atoms µm−2)—a higher loading with Pt nanoparticles does not further increase the photocatalytic activity. Overall, these findings show that anodic TiO2 nanotubes provide a remarkable substrate for Pt extraction and recovery from very dilute solutions that directly results in a highly efficient photocatalyst, fabricated by a simple immersion technique.
CRIS-Team Scopus Importer:2021-11-12
Keywords: dark deposition; hydrogen generation; photocatalysis; single-atom catalysis; TiO

Ordered nanotubular titanium disulfide (TiS2) structures: Synthesis and use as counter electrodes in dye sensitized solar cells (DSSCs) - Licklederer, Markus; Cha, Gi; Hahn, Robert; Schmuki, Patrik (Journal of The Electrochemical Society, 2019)
TiS2 nanotubular structures were synthesized by a high temperature H2S treatment of anodized TiO2 nanotube layers, and their electrochemical activity for a use as counter electrodes in dye sensitized solar cells (DSSCs) was evaluated. During conversion to TiS2 compositional, morphological and structural transformations were monitored. The fully converted TiS2 nanostructures show a high electrocatalytic activity for the I-/I3-oxidation comparable to a nanoparticular platinum layer. For a simplified model a DSSC solar cell efficiency of 6.1% was obtained using the TiS2 nanotube layer as counter electrode, which is very close to values obtained for a Pt reference (6.2%).
CRIS-Team Scopus Importer:2020-02-21

Photocatalytic Hydrogen Generation from Water-Annealed TiO2 Nanotubes with White and Grey Modification - Fu, Fan; Cha, Gi; Wu, Zhenni; Qin, Shanshan; Zhang, Yan; Chen, Yuyue; Schmuki, Patrik (ChemElectroChem, 2021)
In recent years, photocatalytic reactions on anodic TiO2 nanotubes have been intensively investigated. In order to show photocatalytic activity, anodically formed nanotubes need to be crystallized to anatase. This is conventionally done by thermal annealing in air at temperatures 400–600 °C. Recently, a so-called “water annealing” treatment has been reported to be effective to also create a highly active form for photocatalysis. Here we report on the feasibility of using a water annealing treatment of TiO2 nanotubes to create a photocatalyst for H2 production that is as active as conventional thermal annealing. If the water-annealed samples are additionally hydrogenated to a so-called “grey” modification, a further significant improvement of the photocatalytic activity for H2 evolution can be achieved – this without the use of any noble metal co-catalyst. A combination of water annealing, thermal annealing, followed by hydrogenation can deliver a H2 generation activity that is more than five times higher than that achieved by thermal annealing of anodic TiO2 nanotubes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: hydrogenation; optimized water annealing; TiO; titanium (III); water splitting

Photocurrent conversion efficiency of TiO2 nanotube photoanodes in dependence of illumination intensity - Denisov, Nikita; Zhou, Xin; Cha, Gi; Schmuki, Patrik (Electrochimica Acta, 2021)
In the present work, we investigate the photoresponse of TiO2 nanotube photoanodes as a function of the illumination intensity and compare it to compact anodic TiO2 layers. While for the compact layers, in line with expectations, the IPCE is virtually independent of the light intensity, we find for the nanotube morphology a significant increase in the magnitude of the IPCE with lowering the illumination intensity. Moreover, for low light intensities a noticeable change in the IPCE spectra, a substantial slowdown of the transient photocurrent kinetics, an increase of the charge transport time constants, and an anodic shift of the optical flat-band potential is observed. We attribute the sensitivity of the IPCE and other photoresponse effects mainly to a hole accumulation and trapping caused by higher illumination intensities – this effect is particularly strong due to the geometry of the tubes. The observed effects have significant implications for the interpretation and comparability of the TiO2 NT photocurrent data.
CRIS-Team Scopus Importer:2021-03-19
Keywords: IMPS; IPCE; Mott-Schottky analysis; Photoelectrochemistry; TiO2 nanotubes

Photoelectrochemical performance of facet-controlled TiO2nanosheets grown hydrothermally on FTO - Shahvardanfard, Fahimeh; Cha, Gi; Denisov, Nikita; Osuagwu, Benedict; Schmuki, Patrik (Nanoscale Advances, 2021)
Single crystal anatase TiO2nanosheets (TiO2-NSs) are grown hydrothermally on fluorine-doped tin oxide (FTO). By systematically changing the hydrothermal conditions such as reaction time, initial concentration of Ti precursor, F precursor, and HCl as an additive, a wide variety of TiO2-NSs, with different morphologies and faceting have been synthesized. For the different morphologies and different facet ratios (anataseS001/S001+101), the photoelectrochemical response is characterized and compared. We find that for photoanodes in neutral electrolytes, the magnitude of the photocurrent depends strongly on the growth parameters, that is, peak IPCEs can vary from 11.7% to 61%. For a wide range of parameters, the key parameter deciding on the photocurrent is the effective electrochemically active area of the electrode. Only for very high facet ratios >91%, the photoresponse can be strongly influenced by faceting - for samples with aS001/S001+101of 91%, IPCE value of ≈84% is obtained. This work defines not only optimized synthesis conditions for a most effective growth of these single crystalline electrode, but also represents fundamental data for further applications of such electrodes.
CRIS-Team Scopus Importer:2021-02-26

Photoelectrochemical performance of TiO2 photoanodes: Nanotube versus nanoflake electrodes - Zhou, Xin; Denisov, Nikita; Cha, Gi; Hwang, Imgon; Schmuki, Patrik (Electrochemistry Communications, 2021)
In the present work, we compare the photoresponse of vertically erected (VE) single crystal anatase layers with that of widely used TiO2 nanotube layers. These VE-anatase layers were grown hydrothermally, directly on fluorine-doped tin oxide (FTO) glass, and consist of an array of anatase single crystal flakes with preferred (0 0 1) facets. As formed, these single crystal layers are fluorine terminated – this termination can be removed by a thermal treatment in air. We compare the photocurrent magnitude and photocurrent transients using intensity-modulated photocurrent spectroscopy (IMPS). We find that the “de-fluorinated” VE-anatase layers show significantly higher photocurrents than the comparable nanotube layers. This high efficiency of the VE-anatase layers is due to the electron transport being 100 times faster in these single crystal electrodes, provided that the blocking fluorine termination is removed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IMPS; IPCE; Photocurrent transients; TiO; VE-anatase layers

Photoelectrochemical properties of “increasingly dark” TiO2 nanotube arrays - Denisov, Nikita; Qin, Shanshan; Cha, Gi; Yoo, Jeong Eun; Schmuki, Patrik (Journal of Electroanalytical Chemistry, 2020)
“Black” TiO2 nanotube arrays (TNTAs) of different darkness are formed by thermal reduction of anodic TiO2 nanotube layers in H2 atmosphere at different temperatures (300–500 °C), and their (photo-)electrochemical properties are studied by IPCE spectroscopy, transient photocurrent measurements, IMPS, PEIS, CV, and Mott-Schottky analysis. Hydrogenation of the TNTAs leads to the enhancement of their IPCE (by up to 1.5 times), despite increased recombination losses at anodic potentials. Reduced TNTAs demonstrate a “metallic” behavior by a characteristic frequency response of their impedance and phase angle, reduced charge transfer resistance at anodic bias, increased double layer capacitance, and remarkably increased donor densities (up to 7.25 × 1023 cm−3). The observed alterations in the properties of TNTAs after hydrogenation are ascribed to the formation of defects and TiHx.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Anodization; Black titania; Hydrogenation; Nanotubes; Photoelectrochemistry; TiO

Self-assembly and activation of a titania-nanotube based photocatalyst for H-2 evolution - Fu, Fan; Wu, Zhenni; Cha, Gi; Schmuki, Patrik (Chemical Communications, 2021)
Constructing an efficient photocatalyst for H-2 production generally requires the integration of several functional features in and on a semiconductor platform. This is conventionally done by a classic step-by-step synthesis. Here, we report the self-assembly of an amorphous titania nanotube based system when illuminated for extended time in suitable aqueous solutions. Over time, not only photodeposition of a co-catalyst can take place, but also in situ crystallization and morphology changes occur that can provide a higher H-2 production than observed for a classically assembled photocatalyst.
CRIS-Team WoS Importer:2021-07-09

Topographical study of TiO2 nanostructure surface for photocatalytic hydrogen production - Cha, Gi; Lee, Kiyoung; Yoo, Jeong Eun; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work we investigate the photocatalytic hydrogen production (water splitting) activity of different Pt loaded TiO2 nanotube layers. Therefore, we fabricate free standing membranes and fix them in four different configurations: top up (with initiation layer ``grass'' or without) and bottom up (bottom closed or open), then decorate the tubes with various amounts of Pt and measure the open-circuit photocatalytic H2 production rate. We find a strong influence of the configuration with the open top morphology showing the highest photocatalytic hydrogen production efficiency, these nanotubes yield 3.5 times more H2 than the least efficient structure (bottom closed). The work therefore provides valuable guidelines for optimizing TiO2 nanotube layers for photocatalytic applications.
EAM Import::2019-03-13

Water Annealing of TiO2 Nanotubes for Photocatalysis Revisited - Fu, Fan; Cha, Gi; Denisov, Nikita; Chen, Yuyue; Zhang, Yan; Schmuki, Patrik (ChemElectroChem, 2020)
Over the past years, so-called water annealing of TiO2 nanotube (NT) arrays has attracted considerable attention as a tool to enhance the nanotubes’ photocatalytic properties. The present work investigates the effect of different water-annealing treatments on TiO2 nanotubes and compares it to thermally annealed tubes. We find that the most effective water annealing is water immersion of TiO2 NT arrays at 70 °C for several days. The two main effects are i) a partial crystallization of the tubes to anatase, and ii) an etching of the tube walls that leads to a roughening of the walls and, thus, to a higher surface area. Under the best conditions, water annealing is almost as effective in providing enhanced photocatalytic AO7 degradation as a classic thermal annealing of the tubes. We, however, find that water annealed tubes – due to their only partial crystallization – do not perform well when used as photoelectrodes. For photocatalysis, most efficient is a combination of water annealing, followed by thermal annealing, which provides both a larger surface area and a high crystallinity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: anodization; crystallinity; photocatalytic reaction; TiO; water annealing